The Effect of Financial Performance on Audit Opinion with Follow-Up on Audit Recommendations as a Moderating Variable (A Study on Local Governments in West Java for the Period 2019–2023) - Gunarsih, Sabela Shalihati; Romli, Romli (Dinasti Publisher, 2025)
This study, titled The Effect of Financial Performance on Audit Opinion with Audit Recommendation Follow-Up as a Moderating Variable (A Study on Local Governments in West Java for the 2019–2023 Period), investigates the relationship between regional financial performance and audit outcomes issued by Indonesia’s Supreme Audit Board (BPK). This study focuses on the regency and municipal governments in West Java Province as its research objects, covering the period from 2019 to 2023. Financial performance is measured using the fiscal independence ratio, financial efficiency ratio, and revenue effectiveness ratio, while the moderating role of follow-up on audit recommendations (TLRHP) is also examined. Using a quantitative-associative method, the study applies binary logistic regression with Z-Score standardization and interaction terms. The results show that fiscal independence significantly and negatively affects the likelihood of receiving an Unqualified Opinion (WTP), suggesting that greater autonomy without sufficient accountability may increase audit risk. In contrast, financial efficiency, revenue effectiveness, and TLRHP do not show significant effects, nor do they moderate the primary relationships. The overall model demonstrates moderate significance (p = 0.062) and a Nagelkerke R² of 0.202, indicating the presence of other influential factors. These findings imply that fiscal autonomy must be supported by strong internal controls and accountable governance to ensure favorable audit outcomes.